Глорифікація перемоги над русами: епітафія імператора Іоанна Цимісхія - Филипчук, Олександр Михайлович; Fylypchuk, Oleksandr (Інститут історії України НАН України, 2017)
This article represents the lost inscription, the fragment of the epitaph to emperor John Tzimiskes. It gives examples of fictitious epitaphs written by John Geometres, John of Melitene and the anonymous authors in which shows that the ‘heroic narrative’ of epitaph to John Tzimiskes was very similar to these texts. All of this material is presented in detail and analyzed in the article. The author argues that this inscription is glorifying victory over the Rus’.
Keywords: Rus’-Byzantine War, epitaphs, John Tzimiskes, John Geometres, John of Melitene